Effects of the COVID-19 Pandemic on Early Childhood Development and Mental Health: A Systematic Review and Meta-Analysis of Comparative Studies - Sasha Alcon; Sa Shen; Hong-nei Wong; Cynthia R. Rovnaghi; Leni Truong; Jordan K. H. Vedelli; Kanwaljeet J. S. Anand (Psychology International)
From 2020 to 2023, the coronavirus-19 (COVID-19) pandemic exposed children to a variety of adverse childhood events, including parental loss, abuse, and disruption in services, and it exacerbated societal inequities. Studies evaluating the mental health of older children and adolescents reported increases in depression and anxiety symptoms, but no reviews have addressed the effects of the pandemic on preschool children. This systematic review and meta-analysis is the first to explore these effects. The goal was to analyze and synthesize longitudinal cohort studies to determine impact of the COVID-19 pandemic on the development and mental health of young children. Searches of multiple databases were performed for studies published between 2018 and 2023 with pre- and post-pandemic evaluations of the mental health or development of preschool children (aged 0–6 years) using objective measures and according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Cohen’s d effect sizes were calculated for each study that utilized the Strengths and Difficulties Questionnaire (SDQ), Ages and Stages Questionnaire (ASQ), or the Child Behavior Checklist (CBCL). Random-effects mixed models combined the estimates of effect sizes to calculate the overall mean effect size. The meta-analyses included 22,348 children from 16 countries. The analyses showed small increases in emotional symptoms and conduct problems, as well as increases in emotional reactivity, anxiety/depression, withdrawal symptoms, attention problems, and aggressive behaviors. A decrease in fine motor and personal–social skills was noted. Studies not included in these meta-analyses also showed negative effects on language and executive function. This systematic review characterizes the detrimental effects of the COVID-19 pandemic on the mental health and development of preschool children across the world. Our results suggest the vulnerability of early childhood to pandemic-related disruptions, although the heterogeneity in study design and child characteristics may limit some of these conclusions.